The Role of Metacognition and Negative Emotions on Prediction of Abuse Behaviors - M.A Mohammadyfar; M Kafi Anaraki; M Najafi (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The aim of present research was determination of the role of metacognition and negative emotions on prediction of abuse behaviors. Method: In correlational research design which is categorized as descriptive research design, 200 participants selected by available sampling in abandonment clinics in Shahrod city. Out of 200 participants, 128 were addicted and 72 were non addicted persons. Metacognition, anxiety, depression, and stress questionnaires were administered among selected samples. Results: The results of regression analysis showed both variables could be significant predictors in prediction of abuse behaviors. Of metacognition subscales, negative believes about not controlling and risk, and cognitive confidence also of negative emotion subscales depression and anxiety were significant predictors. Conclusion: By consideration of results it could be said by intervention of significant variables the probability of suffering of substance abuse and its relapse could be down.